A Bibliometric Analysis of the Balanced Scorecard - Loso Judijanto (West Science Accounting and Finance, 2026)
The Balanced Scorecard (BSC) has become one of the most influential strategic management frameworks for measuring and improving organizational performance by integrating financial and non-financial perspectives. Over the past decades, BSC research has expanded into various fields, including strategic management, sustainability, performance evaluation, organizational effectiveness, and information management. However, the overall development, intellectual structure, and emerging research directions of Balanced Scorecard literature remain insufficiently explored. This study aims to examine the evolution and research landscape of Balanced Scorecard studies through a bibliometric analysis approach. Data were collected from the Scopus database using relevant keywords related to Balanced Scorecard and analyzed using bibliometric techniques with VOSviewer, including citation analysis, co-authorship analysis, keyword co-occurrence analysis, density visualization, and country collaboration mapping. The findings indicate that Balanced Scorecard research has experienced significant intellectual development, shifting from an initial focus on performance measurement and key performance indicators toward broader themes involving strategic planning, sustainability, environmental management, and organizational alignment. Citation analysis reveals that influential works by Kaplan and Norton, as well as studies related to stakeholder theory, sustainability balanced scorecard, and strategic performance measurement systems, represent the main theoretical foundations of this field. Furthermore, collaboration analysis highlights the global nature of Balanced Scorecard research, with the United States emerging as a central contributor connected with researchers and institutions worldwide. This study contributes to the literature by providing a comprehensive understanding of the development trajectory, dominant themes, and future opportunities in Balanced Scorecard research. Future studies are encouraged to investigate the integration of Balanced Scorecard with digital transformation, artificial intelligence, sustainability frameworks, and data-driven strategic management.